The Influence of Partial Clogging and Pressure on the Behaviour of Geotextiles in Drainage Systems. Issue 4 (1st January 2000) - Gardoni, M.G.; Palmeira, E.M.
Abstract : Nonwoven geotextiles have been used for drainage and filtration in geotechnical engineering works for many years. Concerns related to drainage capacity and clogging potential still remain as factors that restrain a broader use of geotextiles for drainage systems, particularly in major engineering projects. This paper presents the test results of the hydraulic characteristics of partially clogged geotextiles under pressure. Partial clogging can occur during spreading and compaction of soil on geotextiles or throughout the service life of the drainage system. Geotextile specimens, artificially clogged in the laboratory and exhumed from actual field works, were tested to assess their normal and longitudinal permeabilities under different levels of soil impregnation and normal stresses. The results obtained showed that partial clogging significantly influenced the mechanical and hydraulic characteristics of nonwoven geotextiles and that soil impregnation was not necessarily detrimental to the geotextile longitudinal permeability under stress. Comparisons of test and predicted results, confirmed that the expression reported by Giroud in 1996 is a useful tool for the prediction of nonwoven geotextile permeabilities under virgin and soil impregnated conditions. Data on the impregnation levels of geotextile specimens exhumed from actual field works are also presented and discussed.